Eocene Podocarpium (Leguminosae) from South China and its biogeographic implications - Xu, Qingqing; Qiu, Jue; Zhou, Zhekun; Jin, Jianhua (Frontiers in Plant Science, 2015)
Podocarpium A. Braun ex Stizenberger is one of the most common legumes in the Neogene of Eurasia, including fossil fruits, seeds, leaves, and possible flower and pollen grains. This genus is not completely consistent with any extant genera according to gross morphological characters and poorly preserved cuticular structures reported in previous studies. The fossil pods collected from the coal-bearing series of the Changchang Basin of Hainan Island and Maoming Basin of Guangdong, South China, are examined by morphologically comparative work, with special reference to venation patterns and placental position. These distinctive features, as well as the ovule development of pods from different growing stages and the epidermal structure of the pods, as distinguished from previous records lead to the conclusion that these fossils can be recognized as a new species of Podocarpium, P. eocenicum sp. nov. This new discovery indicates that Podocarpium had arrived in South China by the Eocene. Investigation on the fossil records of this extinct genus shows that P. eocenicum is the earliest and lowest latitude fossil data. The possible occurrence pattern of this genus is revealed as follows: Podocarpium had distributed in the South China at least in the middle Eocene, and then migrated to Europe during the Oligocene; in the Miocene this genus reached its peak in Eurasia, spreading extensively across subtropical areas to warm temperate areas; finally, Podocarpium shrank rapidly and became extinct in Eurasia during the Pliocene.